THE BRIDGE to LEARNING is you the TEACHER! - Notar, Charles E.; Sorbet, Stefanie R. (Advances in Social Sciences Research Journal, 2020)
Teachers in today’s classrooms are called to “build a bridge” in order to best meet the needs of their students. Through organizing a classroom, building procedures and rules, fostering intrinsic motivation in students, providing engaging lessons that attain meaningful objectives all while self-reflecting and adjusting along the way are just some of the steps taken by classroom teachers each day in order to best “build a bridge” and meet their students’ needs. Teachers with well-planned and thoughtfully organized classrooms that are constructed with a foundation of support, lead students with routines to succeed. Through accepting feedback and engaging in self-reflection, teachers can adjust lessons and management techniques throughout the school year based on students’ response and achievement. This article provides a guided approach for teachers from setting up the classroom, establishing rules and procedures, to the organization and delivery of content area in a manner that best supports the successes of all students involved.